Determinants of Health Related Quality of Life on People Living in Bandar Abbas, Iran - T Aghamolaei; S Sadat Tavafian; Shahram Zare (Tehran University of Medical Sciences, 2011)
Background: The relationship between socio demographic status and Health Related Quality of Life (HRQOL) has not been well documented in most population of Asian countries including Iran. This study aimed to investigate the determinants of HRQOL in general population living in Bandar Abbas.Methods: This cross sectional study was conducted among general population living in Bandar Abass , Iran from Jun to Jul, 2007. Using a multistage sampling method, a random sample of individuals aged 15 years and over were interviewed through SF-36 questionnaire .Multiple logistic regression analysis were used to predict determinant factors on health related quality of life.Results: Overall, 1675 Iranian adults were interviewed. The majority of the participants were female (50.4%), married (70.9%) and employed (36.8%). The range of education years of most participants (56.7%) were from 6 to 12 years. Female participated in this study had significantly poorer HRQOL than male in all aspects of SF-36 except for Role Emotional (P< 0.001). Furthermore there were significant differences between different age groups in all individually scales and two summaries (P< 0.001). After adjusting for the impacts of other socio demographic factors, variable such as older age, female gender and lower educational level could independently decrease both mental and physical aspect of HRQOL (P< 0.01).Conclusion: Female, older and less educated people are at higher risk of poorer health quality of life in both mental and physical aspects and should be considered as high risk groups in priority health programs.